(untitled) (Scientific journal of the Fergana State University, 2024)
The article analyzes information about the activities of old-style schools and madrasas contained in the “Memoirs” of the outstanding writer and scientist Sadriddin Aini. Taking into account the fact that the author himself studied in an old-style school and madrasah for many years, the reliability of the provided information and the importance of his memoirs as a source on the history of the education system in the Bukhara Emirate are emphasized.